A Meta-learning-driven strategy for adulteration detection in sweet potato starch and vermicelli using Raman spectroscopy - Xijun Wu; Tianhao Du; Shibo Du; Congyu Lei; Heying Zhang; Xuan Zheng; Ruiling Tian (Food Chemistry, 2026)

A 3D correlation spectroscopy framework for spectral feature decoupling: Enabling precise authentication and quantification of dairy cream fat adulteration - Xijun Wu; Xuan Zheng; Shixin Wang; Congyu Lei; Heying Zhang; Tianhao Du; Ruiling Tian (Analytica Chimica Acta, 2026)

Application of instance-based transfer learning for quantitative detection of honey adulteration - Xijun Wu; Heying Zhang; Congyu Lei; Tianhao Du; Xuan Zheng; Ruiling Tian (Food Chemistry, 2026)

Investigation of the Degradation Mechanism of Dibutyl Phthalate in Soil Using Alkali-Modified Biochar and Persulfate Systems - Ruiling Zhang; Xinyu Zhang; Shuang Du; RuiRui Zhang; Jiayong Gao; Youjun Zhang; Jinpeng Liu (Water, Air, & Soil Pollution, 2026)

Sustainable corecovery of lithium, rubidium, and cesium from lepidolite via calcium chloride–sodium lignosulfonate roasting integrated with precipitation–solvent extraction - Guangyu Duan; Ruiling Du; Guangqian Li; Xin Ma; Zhanfang Cao; Hong Zhong; Shuai Wang (Chemical Engineering Journal, 2026)

Characterization of a betaendornavirus isolated from the edible fungus Morchella sextelata - Ruiling Lyu; Junlin Chen; Qing Tang; Du Hai; Tun Wu; Huagang Xiao; Jiatao Xie; Yang Xiao (Archives of Virology, 2025)

Spatiotemporal variability of leaf critical senescence age across northern lands and its key drivers - Xingli Xia; Cuihai You; Ruiling Lu; Ning Wei; Chenyu Bian; Ying Du; Erqian Cui; Songbo Tang; Zhiqin Tu; Jiaye Ping; Kun Huang; Jianyang Xia (Global and Planetary Change, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Facile surface pseudohalide pretreatment of quantum dots for efficient photovoltaics - Zhe Sun; Qinggang Hou; Ruiling Zhang; Jiaxuan Cheng; Jiahua Kong; Keke Wang; Feng Liu; Zhonglin Du; Jianguo Tang (Chemical Engineering Journal, 2023)

New phenotypic characteristics of three tmm alleles in Arabidopsis thaliana - Longfeng Yan; Xi Cheng; Ruiling Jia; Qianqian Qin; Liping Guan; Hang Du; Suiwen Hou (Plant Cell Reports, 2014)